Determinasi Kinerja Pegawai: Tinjauan dari Aspek Kompetensi, Motivasi Kerja, dan Lingkungan Kerja (Studi pada Dinas Perhubungan Kabupaten Rembang) - Mazaya, Saqya Ainil; Ilhami, Susanti Dwi (REVITALISASI : Jurnal Ilmu Manajemen, 2026)
This study aimed to determine and analyze the influence of competence, work motivation, and work environment on the performance of Civil Servants of the Rembang Regency Transportation Agency. The study used a quantitative approach. The sampling technique employed a saturated sample method, thus involving all 53 Civil Servants of the Rembang Regency Transportation Agency. Data collection was conducted using a questionnaire, and the data analysis technique used multiple linear regression with the SPSS program. The results of the study indicated that competence had a significant positive effect on the performance of Civil Servants of the Rembang Regency Transportation Agency, while work motivation and work envoironment had a positive but insignificant effect on the performance. Partially, the three variables explained 24,2% of the variation in the performance of Civil Servants of the Rembang Regency Transportation Agency. Thus, an increase in competence strengthened performance.